2016
DOI: 10.1021/acs.jpcc.5b08703
|View full text |Cite
|
Sign up to set email alerts
|

Active Oxygen Species in Lan+1NinO3n+1 Layered Perovskites for Catalytic Oxidation of Toluene and Methane

Abstract: Layered perovskites possess frameworks that can sustain a larger extent of oxygen nonstoichiometry than perovskites, which makes them possibly more suitable for catalytic applications. However, there is little work in literature concerning the catalytic behaviors of them. In this paper, La n+1Ni n O3n+1 layered perovskites were selected as potential catalysts for catalytic oxidation of toluene and methane. The activation and transmission of active oxygen species over the layered structure were explored by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(50 citation statements)
references
References 60 publications
0
50
0
Order By: Relevance
“…From both desorption and spectroscopic measurements, it was thus concluded that α-O was surface adsorbed oxygen while β-O was lattice oxygen. Building upon these early works, the complexity of these oxygens were further uncovered and their dependence on the chemistry of the perovskites thoroughly discussed [103][104][105][106].…”
Section: Gas Phase Catalytic Reactionmentioning
confidence: 99%
“…From both desorption and spectroscopic measurements, it was thus concluded that α-O was surface adsorbed oxygen while β-O was lattice oxygen. Building upon these early works, the complexity of these oxygens were further uncovered and their dependence on the chemistry of the perovskites thoroughly discussed [103][104][105][106].…”
Section: Gas Phase Catalytic Reactionmentioning
confidence: 99%
“…High-resolution O 1s spectra of SDC, SDC-BS91, and BSZCY91 can be fitted with four peaks (Figure 6d). The peaks centered at ~528.7, ~530.3, ~531.2 and ~532.3 eV are attributed to the lattice oxygen species O 2-, reactive oxygen species, chemisorbed H2O or CO3 2-, and -OHor O 2 , respectively [30][31][32] . Compared to SDC, SDC-BS91 shows a significantly enhanced peak corresponding to chemisorbed H2O or CO3 2-, which is similar to that of BSZCY91.…”
Section: Resultsmentioning
confidence: 99%
“…To date, although TiO 2 ‐based materials are most studied as photocatalysts, other semiconductors are also increasingly concerned for this purpose. Among the groups of metal oxides studied, perovskite‐based catalysts have been confirmed to be effective in catalytic, energy, and environmental applications …”
Section: Introductionmentioning
confidence: 99%
“…Among the groups of metal oxides studied, perovskite-based catalysts have been confirmed to be effective in catalytic, energy, and environmental applications. 6 Perovskites are groups of compounds with the formula ABO 3 , whose crystal structure provides a large opportunity to adjust the absorption of light to the visible region and band gap energy in accordance with specific photocatalytic reactions, having unique photochemical properties, and offer distinct advantages. 7 For example, most titanate perovskites have band gap energy (E g ) greater than 3.0 eV and show good photocatalytic activity under UV radiation.…”
Section: Introductionmentioning
confidence: 99%